Assessing the Direct Economic Effects of Reallocating Irrigation Water to Alternative Uses : Concepts and an Application - Scheierling, Susanne M. (2012)
Irrigation water reallocations are playing an increasingly important role in both developed and developing countries. With growing urban and environmental water demands, rising costs for the development of new water supplies, and irrigated agriculture usually including the least economically valuable use of water, transfers of irrigation water to alternative uses are increasing. However, such reallocations are often controversial, and it is often questioned whether the benefits resulting from these transactions are large enough to outweigh the associated costs. This paper reviews the experience with irrigation water transfers, including the involvement of the World Bank. It discusses the problems of assessing the direct economic effects of reallocations, with a focus on the foregone direct benefits in irrigated agriculture. Because foregone direct benefits cannot easily be directly observed, they need to be estimated. However, assessments have shown widely differing estimates -- even when the same methodology was used. The paper reviews the methodologies and model specifications used for estimating foregone direct benefits; illustrates the impact of different model specifications on the magnitude of estimates of foregone direct benefits based on an application in an example case; and draws conclusions with regard to future efforts in assessing reallocation effects, including calculating adequate compensation for farmers. Because estimating the direct benefits of irrigation expansion is methodologically equivalent to estimating foregone direct benefits from reduced irrigation water supplies, the findings have implications for a broader range of water allocation decisions.